Fertilización foliar inorgánica en el rendimiento de forraje de zea mays var. marginal 28t en Zungarococha - Huerta Guevara, Roberto (2024)
Inorganic foliar fertilizers are an alternative for the production of corn forage as a complement to soil fertilization. The Faculty of Agronomy of the National University of the Peruvian Amazon carries out research on “INORGANIC FOLIAR FERTILIZATION IN THE FORAGE YIELD OF Zea mays.” VAR. MARGINAL 28T IN ZUNGAROCOCHA”. The evaluation time was 45 days after the research work began, with plots of 5 m x 1.2 m (6 m2), with a Random Complete Block Design (RBC), with five treatments and four repetitions, the treatments in study were: T0 (WITNESS), T1 ("MORE LEAVES 20 20-20"), T2 ("EXTRA FOLIAGE 36-6-10"), T3 ("PAWER LEAVES 40-10-10") and T4 (" SUPER FOLIAGE 45-10-10”), where the plant height (m) was 1.99 m. with the T4 treatment (1 kilo of Super foliage 45-10-10/200 liters of water), the weight of green and dry matter was obtained 4.1 and 0.86 kilos per square meter with the T4 treatment (1 kilo of Super foliage 45-10/200 liters of water). 10-10/200 liters of water). Regarding the weight of leaves and stems, 1.6 and 2.5 kilos per square meter were achieved with the T4 treatment (1 kilo of Super foliage 45-10-10/200 liters of water) and in green matter yield of the whole plant. 41,000 kilos per hectare with the T4 treatment (1 kilo of Super foliage 45-10-10/200 liters of water).